The Impact of the Unemployment Benefit System on International Spillover Effects - Thomas Beissinger; Oliver Büsse (Institute for the Study of Labor (IZA), 2003)
Based on a two-country model it is scrutinized how the structure of the unemployment benefit system affects the consequences of idiosyncratic labor market shocks on real wages and unemployment in other countries. International spillover effects are caused by changes in world real income. The paper provides new insights on how changes in world real income affect labor demand and the wage bargaining process. The analysis of the interaction of shock spillovers and benefit system focuses on two-tier as well as pure earnings-related and flat-rate benefit systems.
Keywords: E24; F41; J23; J51; J65; 330; benefit system; unemployment; real wages; open economy; wage bargaining; Arbeitslosenversicherung; Reallohn; Schock; Gesamtwirtschaftliche Produktion; Konjunkturzusammenhang; Theorie